Empowered learning in school: A scoping review - Anto Titus; Peter Varkey Muttungal (Institute of Advanced Engineering and Science, 2023)
A high degree of motivation, a sense of commitment, self-efficacy and the ability to make the right choices are the characteristics of empowered learners. With education being seen as preparation for life, educators are increasingly pressured to develop curriculum and pedagogy that assist learners to become empowered. Based on the theoretical framework developed by Arksey and O’Malley, the present study reviewed 16 empowered learning intervention studies at the school level published between the years 1995 and 2021 as well as provides an extensive summary of empowered learning enhancing interventions conducted in schools. This study highlights the concept of empowered learning, features and scope of interventions directed towards empowered learning of students at schools and the role of empowered learning in schools. Notwithstanding varied intervention results, the findings of this study indicate that empowered learning interventions produce highly motivated students with a sense of commitment and self-efficacy. This review also identifies the need for more pure experimental studies and a commonly accepted theory on empowered learning as a single concept.